2016
DOI: 10.1515/zkri-2015-1914
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld analysis of the kryptoracemate: bis(mefloquinium) chloride p-fluorobenzenesulphonate

Abstract: The crystal structure analysis of the bis(mefloquinium) chloride p-fluorobenzenesulphonate salt reveals a rare example of a kryptoracemate given that the cations exhibit a non-crystallographic enantiomeric relationship. The conformations of the cations are based on a skewed letter L with the (piperidinium-2-yl)methanol group sitting almost normal to and directed away from the quinolinyl residue. The most prominent feature of the molecular packing is the formation of supramolecular helical chains along the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The Hirshfeld surface calculations were carried out for the polymorphs 1 and 2 in accord with a recent study on an organic salt [39]. The results provide additional insight into the influence of non-covalent interactions on their molecular packing and assist in differentiating between the independent species found in 1 and 2.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…The Hirshfeld surface calculations were carried out for the polymorphs 1 and 2 in accord with a recent study on an organic salt [39]. The results provide additional insight into the influence of non-covalent interactions on their molecular packing and assist in differentiating between the independent species found in 1 and 2.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…A review of this phenomenon has appeared for organic compounds (Fá biá n & Brock, 2010) where such behaviour is found in only 0.1% of structures. There are about 30 mefloquine/derivatives in the Cambridge Structural Database (Groom et al, 2016) and of these, there are two examples of kryptoracemates (Jotani et al, 2016;Wardell, Wardell et al, 2016). Further, in a very recent study, 34 new mefloquine salts were reported of which two were kryptoracemates (Engwerda et al, 2019).…”
Section: Database Surveymentioning
confidence: 99%
“…The Hirshfeld surfaces calculated for (I) were performed in accord with recent studies (Jotani et al, 2016) Intra-and intermolecular interactions (Å , ) for (I).…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%